2017
DOI: 10.1016/j.renene.2017.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of abandoned oil and gas wells for geothermal energy production

Abstract: This paper presents an investigation on the suitability of abandoned wells in California for Enhanced Geothermal Systems (EGS) and low temperature deep Borehole Heat Exchanger (BHE) applications. The study identifies three counties characterized by high numbers of abandoned wells, medium to high crustal heat flows (75-100 mW/m 2 ), and suitable sedimentary geology: Santa Clara, Monterey, and Santa Barbara. Thermal gradients range between 4 and 7.3°C /100 m and enable access to the bottom hole temperatures betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…The results showed that the simulated outlet temperature had a good compromise with experiment data. Caulk and Tomac analyzed the outlet temperature of DBHE with 1000‐m depth by FEM. They found that outlet fluid temperature can be up to 40°C when the temperature gradient is greater than 7°C/100 m. On the basis of the Finite Element subsurface FLOW system (FEFLOW) code, Welsch et al studied the thermal extraction rate of DBHE under inlet fluid temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the simulated outlet temperature had a good compromise with experiment data. Caulk and Tomac analyzed the outlet temperature of DBHE with 1000‐m depth by FEM. They found that outlet fluid temperature can be up to 40°C when the temperature gradient is greater than 7°C/100 m. On the basis of the Finite Element subsurface FLOW system (FEFLOW) code, Welsch et al studied the thermal extraction rate of DBHE under inlet fluid temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The model-based analysis [7] of Vilfortune-Trekate, the large European oil field, shows that one well can produce 4 MW of thermal and 400 kW of electric power at an estimated cost of electricity of 0.05 euro/kWh (Italian consumers). In [8] the heat-flux density in wells of 75 -100 mW/m 2 for geological formations of California (Santa Clara, Monterey and Santa Barbara) were investigated. Work [10] shows the significant potential of depleted and abandoned oil wells in Pakistan from the point of view of geothermal energy of oil and gas reservoirs with significant water-flood operation in the end.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, data collected only in California indicate the number of over 140,000 wells. Most of these wells were plugged due to a decline of oil and gas productivity, while other wells were exploratory (Caulk and Tomac 2017). Well reconstruction can be a much better option for geothermal developers than drilling a new well.…”
mentioning
confidence: 99%
“…The lack of formal and administrative problems, which are usually long and burdensome in the case of drilling new wells, is also of great importance. The necessary condition for obtaining such benefits is the correct design and execution of reconstruction work (Caulk and Tomac 2017;Røksland et al 2017;Nian and Cheng 2018a, b;Capuano 2016;.…”
mentioning
confidence: 99%
See 1 more Smart Citation